Arbuscular mycorrhizal fungi and Rhizobium enhance the growth of Samanea saman (trembesi) planted on gold-mine tailings in Pongkor, West Java, Indonesia - Luluk Setyaningsih; FIRLI AZHAR DIKDAYATAMA; ARUM SEKAR WULANDARI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Setyaningsih L, Dikdayatama FA, Wulandari AS. 2020. Arbuscular mycorrhizal fungi and Rhizobium enhance the growth of Samanea saman (trembesi) planted on gold-mine tailings in Pongkor, West Java, Indonesia. Biodiversitas 21: 611-616. Revegetation of severely degraded lands, such as gold-mine tailings, requires comprehensive approach including the selection of appropriate tree species and the improvement of soil fertility with the application of microorganisms. This study aimed to analyze the growth of trembesi (Samanea saman (Jacq.) Merr) seedlings inoculated with Arbuscular Mycorrhizal Fungi (AMF) and rhizobial bacteria (RB) on gold-mine tailings in Pongkor, Bogor, West Java, Indonesia. The AMF, RB, and mixture of AMF and RB were inoculated into S. saman seedlings and then the seedlings were grown on gold mine tailings land. Seedling growth, AMF infection and RB nodulation were observed after 12 weeks after planting. The results showed that the treatments facilitated AMF colonization by up to 20.7% and RB nodulation up to 22 nodules per plant. The inoculation of S. saman seedlings with AMF and RB significantly increased the growth on diameter, biomass, and root length, with values of root-to-shoot ratio of 3.1-4.3. The roots of S. saman seedlings were also able to penetrate the depth of the tailings solum. These results showed that AMF and RB application effectively increased the growth of S. saman seedlings in the gold tailings field.